Neurophysiologic Monitoring and Pharmacologic Provocative Testing for Embolization of Spinal Cord Arteriovenous Malformations - Niimi, Yasunari (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: Embolization of a spinal cord arteriovenous malformation (SCAVM) is still considered risky. We evaluated the efficacy and reliability of pharmacologic provocative testing with neurophysiologic monitoring in the embolization of SCAVMs. METHODS: We retrospectively analyzed results of 60 provocative tests during 84 angiographic procedures (in 52 patients) with intended endovascular embolization. Tests included 47 sodium amytal and 56 lidocaine injections. All procedures were performed with general anesthesia and monitoring of cortical somatosensory evoked potentials (SEPs) and transcranial motor evoked potentials (MEPs). For provocative testing, 50 mg of amytal and 40 mg of lidocaine were consecutively injected through a microcatheter placed at the position of intended embolization. If SEPs and MEPs did not change, embolization was performed with n-butyl-cyanoacrylate (NBCA). If SEPs or MEPs changed, NBCA embolization was not performed from that catheter position. RESULTS: One false-negative result occurred, with an increase in spasticity after embolization. Nineteen positive results occurred: four after amytal injection and 15 after lidocaine injections. Seven injections in a posterior spinal artery feeder resulted in loss of SEPs or MEPs. Eleven injections in the anterior spinal artery feeder and one in the posterior inferior cerebellar artery feeder resulted in loss of MEPs. CONCLUSION: Provocative testing with amytal and lidocaine combined with neurophysiologic monitoring had a high negative predictive value and was a useful adjunct for SCAVM embolization. Both amytal and lidocaine should be used as provocative agents, and both SEPs and MEPs should be monitored.